2019
DOI: 10.1080/02713683.2019.1635166
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surrogate Biomarkers for the Prediction of Patients at Risk of Low Macular Pigment in Type 2 Diabetes

Abstract: Purpose: This cross-sectional study compared macular pigment (MP) levels among persons with Type 2 diabetes relative to healthy controls. Additionally, a range of behavioral, anthropometric, clinical and serum measures were explored as possible predictors of low MP optical density (MPOD) in diabetes. Methods: Two health status groups; Group 1: Type 2 diabetes (n = 188), and Group 2: Healthy controls (n = 2,594) completed a full MP assessment using customized heterochromatic flicker photometry, as part of The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Clinical studies implicate MPOD depletion, as well as low serum levels of lutein and zeaxanthin, may represent a novel clinical feature of DR; one that is likely contingent upon several metabolic perturbations associated with chronic hyperglycemia in type 1 and type 2 diabetes. Reports from observational studies are consistent in demonstrating carotenoid levels (measured both in serum and the macular pigment) are further reduced among diabetic patients with clinically evident retinopathy ( Table 3 ) [ 19 , 25 , 34 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. In fact, one study found that lower plasma concentrations of lutein and zeaxanthin were significantly associated with greater risk of incident maculopathy as well as disease progression in patients with T2DM [ 109 ].…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Clinical studies implicate MPOD depletion, as well as low serum levels of lutein and zeaxanthin, may represent a novel clinical feature of DR; one that is likely contingent upon several metabolic perturbations associated with chronic hyperglycemia in type 1 and type 2 diabetes. Reports from observational studies are consistent in demonstrating carotenoid levels (measured both in serum and the macular pigment) are further reduced among diabetic patients with clinically evident retinopathy ( Table 3 ) [ 19 , 25 , 34 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. In fact, one study found that lower plasma concentrations of lutein and zeaxanthin were significantly associated with greater risk of incident maculopathy as well as disease progression in patients with T2DM [ 109 ].…”
Section: Resultsmentioning
confidence: 67%
“…Consequently, 103 records were excluded based on article type, with an additional 148 records excluded due to the aforementioned inclusion criteria for clinical and preclinical studies. Finally, 30 records were identified to be eligible for full-text assessment, of which, 18 studies were included in the final review: seven preclinical studies [ 102 , 103 , 104 , 105 , 106 , 107 , 108 ], nine observational clinical studies [ 19 , 25 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ] and two interventional clinical trials [ 34 , 116 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be used in food as spices, colorants, and antioxidant agents [ 9 , 10 , 11 ]. Moreover, carotenoids have healthful properties and can prevent chronic diseases such as different kinds of cancer, cardiovascular disease, type 2 diabetes, and atherosclerosis [ 12 , 13 , 14 ]. Many studies have shown that organic vegetables contain more bioactive compounds, including carotenoids, than conventionally grown vegetables [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%